2006
DOI: 10.1007/s00520-006-0109-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of chemotherapy-induced nausea and vomiting on health-related quality of life

Abstract: Despite antiemetic prophylaxis, CINV is still prevalent and often impacts the daily life of patients in Italy, especially in the delayed phase. The duration more than the severity seems to be responsible for the impact of CINV on the patients' daily lives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(89 citation statements)
references
References 25 publications
(15 reference statements)
4
77
0
8
Order By: Relevance
“…Nausea is, from the patients' own perspective, even more negative than vomiting, while, in contrast, medical providers tend to consider their patients' vomiting worse than nausea, with the risk to underestimate the latter [6,7] . CINV has extremely negative consequences by reducing daily functioning and quality of life (QoL) [8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Nausea is, from the patients' own perspective, even more negative than vomiting, while, in contrast, medical providers tend to consider their patients' vomiting worse than nausea, with the risk to underestimate the latter [6,7] . CINV has extremely negative consequences by reducing daily functioning and quality of life (QoL) [8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Benché la quantificazione dei costi e dell'impatto di CINV nella pratica clinica sia di estrema importanza per l'allocazione delle risorse nei confronti di nuove terapie antiemetiche, gli studi che trattano il costo di malattia sono abbastanza ridotti [16][17][18][19][20] parte dei lavori tende a prendere in esame gli aspetti farmacoeconomici di un singolo antiemetico, e spesso solo in relazione alla CINV in fase acuta. L'unico studio specifico che ha valutato il costo di malattia nella realtà italiana che siamo riusciti a reperire è il lavoro di Ballatori e coll.…”
Section: Costo DI Malattiaunclassified
“…Studies have shown that chemotherapy-induced nausea and vomiting reduce well-being [11], quality of life [3,30,32], performance of daily activities [30,33,34], ability to socially interact [30] and increases anxiety and low mood [43]. However, [30] radiotherapy-induced nausea is generally less frequent and less severe than chemotherapy-induced nausea [42] and it is not known to what extent these findings are also valid for patients with nausea during radiotherapy.…”
Section: Introductionmentioning
confidence: 99%